Optimised image retargeting using aesthetic‐based cropping and scaling. Issue 1 (1st February 2013) - Liang, Yun; Su, Zhuo; Wang, Chuntao; Wang, Dong; Luo, Xiaonan
Abstract : Image retargeting is a critical technique in displaying images on devices with different resolutions. This study presents a new image retargeting algorithm based on aesthetic‐based cropping and scaling. A composite measurement is first constructed under the guidelines of composition aesthetics in photographing. An aesthetic‐based cropping is proposed to yield an optimal candidate retargeted image with maximum aesthetic value computed via a constructed composite measurement. The optimal candidate is uniformly scaled to obtain the retargeted image of target size. Some subjective and objective assessments demonstrate that the proposed scheme significantly improves the aesthetics of retargeted images while preserving the important objects. It also achieves better performance in terms of aesthetics than a number of conventional image retargeting approaches.